Kahoot for Teaching and Learning Bioethics - Tulcanaza Huertas, William Aníbal; Miranda Realpe, Luz Acacia (SATHIRI, 2025)
Teaching bioethics in nursing can be challenging due to the high theoretical load, which may lead to disengagement among students. This study aimed to evaluate gamification strategies using the Kahoot! tool to improve the teaching-learning process of bioethics in the Nursing Degree Program at the Universidad Politécnica Estatal del Carchi. A mixed-methods approach was employed, with a quasi-experimental and pre-experimental design. The study was conducted with 17 bioethics students and one teacher at the aforementioned university. Data collection involved interviews with the teacher and Pre-Test and Post-Test surveys with the students. Statistical analysis included Wilcoxon signed-rank tests and Kendall’s Tau correlations. Results showed a significant improvement in student performance after the implementation of Kahoot!, with positive ranks or ties between pre- and post-test measurements. Additionally, positive relationships were identified between some variables. In conclusion, the use of Kahoot! emerged as a positive strategy for student learning, motivating them, integrating them, and helping them retain the knowledge acquired in bioethics. This approach could offer an effective alternative to conventional teaching methods in the field of medicine.